The Relationship Between Family Support on the Care Process of Lulmon Tubercolosis Patients in the Working Area of Rahuning Health Center, Rahuning District, Asahan Regency - Arsiaty; Manik, Andre Bastian (PT Inovasi Pratama Internasional, 2023)
The success of tuberculosis treatment depends on the patient's knowledge and support from the family. There is no self-effort or motivation from the family who does not provide support for complete treatment. It will affect patient adherence to taking the drug. A study was conducted to find out whether there is a relationship between family support and the patient's recovery process. Pulmonary Tuberculosis in the Working Area of the Rabuning Health Center, Rahuning District, Asahan Regency in 2019 This research was conducted in July-September 2019 with a population of 32 respondents. The sampling was carried out using total sampling. The results of this study found that from 15 respondents who received emotional support, all of them received healing compared to less supportive 6 respondents out of 8 respondents, who did not support 1 respondent and 9 respondents Out of 15 respondents who received information support all got healing compared to less supportive 6 respondents and 10 respondents, who did not support 1 respondent out of 9 respondents. Of the 10 respondents who received instrumental support, all of them got healing compared to less supportive, 11 of 14 respondents who did not support the respondent and 8 respondents. the patient did not experience recovery at all. This research is expected to provide benefits to families in assisting patients in obtaining recovery by providing emotional support, informational support, instrumental support and appreciation support regarding the importance of family support in helping to increase patient knowledge so that it can affect recovery.